Breaking Gender Stereotypes in Enola Holmes 2(2022): Memecahkan Stereotip Gender di Enola Holmes 2(2022) - Putri Jayastu, Nathania Amany (LITERA KULTURA : Journal of Literary and Cultural Studies, 2023)
These days, one of the issues that is often raised in literature works is about feminism and gender issues. Women has been frequently discriminated against in the society due to the negative stereotypes. This issue is widely represented in literary works. One piece of literature that portrays feminism and gender stereotypes is Enola Holmes 2 (2022). Enola Holmes 2 (2022) is a film that tells about the struggle of Enola Holmes and other women in the Victorian Era to face various gender stereotypes in society. This research is done with the aim to analyze the depiction of gender stereotypes in Enola Holmes 2 (2022) and how female characters in Enola Holmes 2 (2022) break gender stereotypes. To analyze the film, the researcher used Gender and Feminism Theory by Butler (1999) by exploring gender stereotypes and feminism in society. The analysis reveals that Enola Holmes 2 (2022) depicted several gender stereotypes: women seen as weak human beings by society, women as feminine figures, women as submissive human beings, and women as emotional human beings. Moreover, to break the gender stereotype there are several actions that is done by the female characters in Enola Holmes 2 (2022) which is tried to become equal, starting feminism movement to raise public awareness that women should have equal human right, fighting together with ally as support system, and doing rebellion to show that women as a great power as a human being. Keywords: Gender Stereotypes; Feminism; Judith Butler; Gender Role.